Digital appendix: Glyco-STORM: lectins as a new labeling tool to decipher the nanoarchitecture of cells - Schröter, Helene Gregoria (Universität, 2025)
This is the digital appendix to the dissertation with the title "Glyco-STORM: lectins as a new labeling tool to decipher the nanoarchitecture of cells" by Helene Schröter. In this study, previous obstacles in studying the glycome were overcome by combining fluorophore-conjugated lectins - carbohydrate-binding proteins - with super-resolution microscopy. This approach was termed Glyco-STORM and led to the establishment of new anatomical markers to analyse the architecture of cell organelles and synaptic specializations on the nanoscale. Since lectins reflect the carbohydrate-specific morphology of the underlying structures, the results enable a new - ‘glyco-centric’ - picture of cell machineries, achieving a new level in understanding the function of biological systems. Cracking the ‘sugar code’ by using lectins as labels in a biological context could bring a breakthrough in understanding health and disease of organisms.